The epidemic of methylisothiazolinone contact allergy in Europe: follow-up on changing exposures - Uter, Wolfgang; Aalto‐Korte, K.; Agner, T.; Andersen, K. E.; Bircher, A. J.; Brans, R.; Bruze, M.; Diepgen, Thomas L.; Foti, C.; Arnau, A. Giménez; Gonçalo, M.; Goossens, A.; et al. (Journal of the European Academy of Dermatology and Venereology, 2020)
Background Methylisothiazolinone (MI) has caused an unprecedented epidemic of contact allergy in Europe and elsewhere. Subsequently, regulatory action has been taken, at least in Europe, aiming at reducing risk of MI sensitization. Objective To follow-up on the prevalence of contact allergy to MI in consecutively patch tested patients and assess the spectrum of products containing MI or methylchloroisothiazolinone (MCI)/MI in patients positive to MI which elicited current allergic contact dermatitis. Methods A cross-sectional survey was performed in 2016 and 2017, including all adult patients patch tested with the baseline series (including MI 0.2% aq.) between 1 May and 31 October at 14 centres in 11 European countries. Patients with positive reactions (+ to +++) to MI were further examined regarding history, clinical characteristics and eliciting products, which were categorized into 34 types and 4 classes (leave-on, rinse-off, household, occupational). The results were compared with the reference year 2015. Results A total of 317 patients, n = 202 of 4278 tested in 2016 (4.72%) and n = 115 of 3879 tested in 2017 (2.96%), had positive reactions to MI; the previous result from 2015 was 5.97% (P < 0.0001). The share of currently relevant contact allergy among all positive reactions declined significantly as well (P = 0.0032). Concerning product classes, a relative decline of leave-on and a relative increase of rinse-off and household products was noted. Conclusion The prevalence of MI contact allergy decreased by 50% from 2015 to 2017. As a consequence of regulation, the share of cosmetics products (leave-on in particular) eliciting allergic contact dermatitis is decreasing. The chosen method of analysing causative products in sensitized patients has proven useful to monitor effects of intervention.
First published: 16 August 2019
Gesehen am 12.05.2020